Gastropoda Community Structure in Seagrass Ecosystems in Bama Waters of Baluran National Park, Situbondo, East Java - Widhi, Raut Nugrahening; Paluphi, Raut Wahyuning; Irham, Irham (Agrikan Jurnal Agribisnis Perikanan, 2024)
Gastropods are one of the macrobenthos associated with seagrass ecosystems. The purpose of this research is to determine the structure of the gastropod community in the seagrass ecosystem in the Bama waters of Baluran National Park. Collecting data on gastropods in seagrass ecosystems uses quadrat transects. The research was conducted in February 2024. Based on the research results, it was found that the richness of gastropod species in the seagrass ecosystem in the waters of Baluran National Park was in the low category at each station. The gastropod species diversity index value in this study was in the low category. The evenness index has a stable category, while the dominance index in this study does not have species dominance in gastropods. Seagrass density in this study was in the rare and dense categories.